Señal acústica y redescripción de Gongrocnemis (Gongrocnemis) munda Brunner von Wattenwyl, 1895 (Orthoptera: Tettigoniidae) - Fernández-Azuara, Geovany J.; Barrientos-Lozano, Ludivina; Rocha-Sánchez, Aurora Y.; Zaldívar-Riverón, Alejandro; Almaguer-Sierra, Pedro; Correa-Sandoval, Alfonso (Instituto de Ecología, A.C., 2020)
In the Orthoptera of the superfamily Tettigonioidea acoustic signals are of special interest since they play an important role in the process of pair formation and are directly involved in intraspecific male-female recognition. The calling signal usually allows the male to attract individuals of the opposite sex at short or long distance. In this work, we present the acoustic signal of Gongrocnemis (Gongrocnemis) munda (Tettigoniidae: Pseudophyllinae) and provide a brief redescription of this species, in particular of the female not formally described previously. Specimens of G. (G.) munda were collected in San Felipe Orizatlán, (1♂: 1♀; 27.XI.2017) and Ixcatlán, Huejutla de Reyes (2♂: 2♀; 22.I.2013), Hidalgo, México. G. (G.) mexicana was collected in Ciudad del Maíz, San Luis Potosí (1♀; 19.VII.2003). Males produce the calling acoustic signal mainly at night, and it is composed of paired-echemes. The acoustic signal may be produced uninterruptedly for long periods, 1 h or more. Males of G. (G.) munda produce 6.0 ± 0.9 (s.d) echemes per minute (n=30 min; three males, 10 min each). Duration per paired-echeme is 3.97 ± (s.d) 1.2 s (2.7-8.0 s) (n=30 echemes). Frequency analysis showed the highest energy release between 16-40 kHz, with a fi peak in the range of 20-38 kHz. The female is similar to the male, but more robust. The general body color is olive-green, with cream spots and brown marks. The average length is 32.7 ± 1.5 mm (n=3). The ecosystem this species lives on is tropical evergreen and oak forest; it is found usually on the foliage or trunk of trees. During the day, adults remain quiet and hidden, being active at night.